Rozumění pedagogickému jsoucnu: k duchovní obnově pedagogiky a škol. Understanding pedagogical existence: Contribution to the spiritual renewal. - Ries Lumír (Czech Pedagogical Society, 2012)
Similarly to all pedagogical activities, in view of the present situation of man and his world, pedagogical existence is expected to undergo profound transformations. Understanding the nature of the hierarchical structure of pedagogical existence is a potential precondition of these transformations. The hierarchical structure contains the following seven levels: 1. rectification of human circumstances; 2. interpersonal relations; 3. specificity of the spheres of cognition and behaviour; 4. interconnection between the spheres of cognition and behaviour; 5. the cultural, philosophical(ideological) potential of cognition and behaviour; 6. learning and experiencing the meaning, higher values and spirituality, 7. deeds, action, behaviour, utilisation. The first, basic level and the top levels, i.e. from the fifth to the seventh, can be consideredpreconditions of desirable transformations within education.